Penetasan Telur Untuk Meningkatkan Pendapatan Peternak Ayam Desa Bandar Khalipah Kecamatan Percut Sei Tuan - Lumbantoruan, Henry Hasian; Simanjuntak, Melvin Emil; Simanjuntak, Benrad Edwin; Saragi, Jandri Fan HT (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2024)
Local breed chicken farming is one of the businesses that is still quite promising to be run today, including by service partners who live in Bandar Khalipah Village, Percut Sei Tuan District, Deli Serdang Regency, who currently raise 300 chickens. The price of its DOC is still relatively high for local breed chicken with prices ranging from Rp. 9,000,- per head, and partners always buy DOC every time they enlarge. There is potential for business development from selling DOC chickens, but it is hampered because partners do not yet have egg incubator machines. The gross profit obtained from the sale local breed chickens is still around 20 percent. Partners who do not have their own egg incubator machines are a problem currently being faced by partners, so the proposing team offers a solution in the form of designing an automatic egg incubator machine and training in its operation to overcome this problem. The donated machine is capable of incubating 300 eggs for each process.